A narrativa de Deus: a força da teologia narrativa - Oliveira, Maria Goretti de (2018)
This research aims to demonstrate the strength of narrative language in Theology and how Christianity salvation's message is transmitted through this literary genre. The study was conducted from the method of narrative analysis which considers the narrative strategies in order to reach the author's Theology. Therefore, the literary categories are identified with the purpose of presenting how the biblical narrative becomes Theology with the intention to express the communities' faith experience. For that purpose it is identifies how the narrator constructs the narrative and are analyzes the strategies used with the intention the provocating the construction of meaning while reading. The creation of the plot, the narrator, the characters, the time, the space and the narrative focus are literary components used to represent the theology of the author and his confession of faith. T his analysis Will demonstrate which theological contents comes up from the narrative at Acts 9:1-19a. The hypothesis defended that the practice of literary genre has a fundamental importance in Theology. The nature of this research is theoretical and bibliographical. Its itinerary was developed by readings, reflections and analysis. All of this was supported by a selected bibliography about the subject. It gathered publications about the narrative literary genre, and the narrative analysis. In addition, in this study, were chosen biblical commentaries about the text